2022
DOI: 10.1039/d2ra02236b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced photocatalytic H2 evolution over covalent organic frameworks through an assembled NiS cocatalyst

Abstract: We constructed a novel hybrid photocatalyst by assembling NiS through a milder method. Under visible light irradiation, controlled NiS/TpBD-COF composites can readily optimize photocatalytic performances without a noble cocatalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 52 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…The heterostructure shows HER activity up to 3.84 mmol h −1 g −1 under visible light irradiation (Figure 6g). [68] All these results suggest that, as in many of the well-studied heterostructure photocatalysts, some metal sulfides are promising candidates to replace Pt in photocatalytic HER for COF. It is expected that more metal sulfides, especially the 2D nanosheets, could be explored as Pt-free photocatalytic HER cocatalysts for COF.…”
Section: Photocatalytic Her Based On Cof/mss Heterostructurementioning
confidence: 97%
“…The heterostructure shows HER activity up to 3.84 mmol h −1 g −1 under visible light irradiation (Figure 6g). [68] All these results suggest that, as in many of the well-studied heterostructure photocatalysts, some metal sulfides are promising candidates to replace Pt in photocatalytic HER for COF. It is expected that more metal sulfides, especially the 2D nanosheets, could be explored as Pt-free photocatalytic HER cocatalysts for COF.…”
Section: Photocatalytic Her Based On Cof/mss Heterostructurementioning
confidence: 97%
“…Dramatic increment was observed for the CdS-COF hybrid, and the optimum H 2 generation was found when the CdS to COF ratio was maintained at 90:10 (wt %). Conversely, Zhang et al examined the potential of NiS as a cocatalyst . A typical TpBD COF was synthesized and loaded with NiS to result in NiSX-BD composites (X = wt % of NiS).…”
Section: Covalent Organic Framework-based Photochemical Electrochemic...mentioning
confidence: 99%
“…Conversely, Zhang et al examined the potential of NiS as a cocatalyst. 32 A typical TpBD COF was synthesized and loaded with NiS to result in NiSX-BD composites (X = wt % of NiS). TEM analysis of the composite revealed that NiS nanoparticles strongly adhered to the COF surface.…”
Section: Covalent Organic Framework-based Photochemical Electrochemic...mentioning
confidence: 99%
“…The surface of NiS is easily functionalized by some groups, which can better combine with other semiconductor materials. [43,44] Several reviews have been published for the elimination of pollutants using photocatalysis technology with cocatalysts. Sharma et al [45] presented the synthesis strategy and structural properties of NiS photocatalysts and summarized the different types of heterojunctions of NiS with metal, metal oxide, and carbide.…”
Section: Introductionmentioning
confidence: 99%
“…The surface of NiS is easily functionalized by some groups, which can better combine with other semiconductor materials. [ 43,44 ]…”
Section: Introductionmentioning
confidence: 99%